The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.21037/apm-20-1539
|View full text |Cite
|
Sign up to set email alerts
|

A postoperative comparison of high-flow nasal cannula therapy and conventional oxygen therapy for esophageal cancer patients

Abstract: Background: Hypoxaemia in post-surgical patients of esophageal cancer (EC) is common in thoracic departments. However, few studies have investigated the role of high-flow nasal cannula (HFNC) compared with conventional oxygen therapy (COT).Methods: A retrospective study was implemented to enroll hypoxemic patients after esophagectomy who were treated by HFNC or COT immediately after extubation between January 2019 and December 2019.We compared the effect of HFNC or COT in patients regarding the vital signs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…We found similar results in the meta-analysis of Du et al (23). In different operations, compared with COT, the use of HFNC on patients after surgery has been shown to prevent atelectasis (24)(25)(26)(27). For cardiac surgery, especially in obese patients, the prevention of atelectasis by HFNC is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…We found similar results in the meta-analysis of Du et al (23). In different operations, compared with COT, the use of HFNC on patients after surgery has been shown to prevent atelectasis (24)(25)(26)(27). For cardiac surgery, especially in obese patients, the prevention of atelectasis by HFNC is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pulmonary complications mainly include atelectasis, pneumonia and respiratory failure, which usually cause to hypoxemia. Previous studies showed that perioperative interventions, including protective ventilation strategy [18,19], high-ow nasal cannula [20], epidural analgesia and regional anesthesias [21], respiratory physiotherapy [22,23], can reduce PPCs and improve oxygenation with thoracic and abdominal surgery. However, no high-quality evidence was found for interventions to reduce incidence of PPCs [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has a disadvantage that it can not provide reliable FiO 2 or reduce patients' work of breathing. 16,17 HFNC can make up for its limitations. As for the possible reason, HFNC can increase mucus clearance rate, and improve dead space volume and lung mechanics, thereby improving the tidal volume and ensuring effective alveolar ventilation.…”
Section: Discussionmentioning
confidence: 99%